New approach methodologies to assess wanted and unwanted drugs-induced immunostimulation - Valeria Bettinsoli; Gloria Melzi; Irene Marchese; Sofia Pantaleoni; Francesca Carlotta Passoni; Emanuela Corsini (Current Research in Toxicology, 2025)
This review examines various classes of drugs, focusing on their therapeutic and adverse effects, particularly in relation to immunostimulation. We emphasize the potential of new approach methodologies (NAMs) to study both expected and unexpected immunostimulatory effects. By evaluating the modes of action of different immunostimulatory drugs, we aim to provide insights into effectively assessing unwanted immunostimulatory responses. The review begins by exploring drugs that stimulate the immune system—including immunostimulants, monoclonal antibodies, chemotherapeutics, and nucleic acid-based drugs—to outline NAMs that could be employed to evaluate immunostimulation.